TECHNOLOGICAL CONVERGENCE IN VISUAL ARTS: BLENDING DIGITAL FABRICATION WITH TRADITIONAL CRAFTING - Barla, Usha Kiran; Kataria, Ansh; K, Keerthika; Ramtirthkar, Chandrashekhar Ramesh; P, Kalpana; Baskar, V. Vijaya (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The intersection of digital fabrication technologies and older crafting setting is reshaping the artistic production and creative potential of the contemporary visual arts by broadening the production of materials, experimentation with materials and inter-disciplinary cooperation. The 3D printing, laser cutting, CNC machining, and improved digital modeling software allow artists to create complicated geometries, mechanize fabrication techniques, and quickly model artistic ideas. Meanwhile, the rich material expertise, cultural traditions, and sense of touch, which digital technologies do not have the power to reproduce, are still preserved through the traditional craft methods, such as handcrafted sculpture, textile weaving, ceramics, and woodcraft. The study offers a discussion on how convergence in technology supports hybrid forms of artistic practice that involve the use of computers in the construction of artists and their artworks through manual craftsmanship. It explores how digital fabrication technologies are used in the creative processes of artists, evaluates the importance of conventional craft knowledge systems, and explores new forms of partnership between artists, engineers and artisans. The paper also addresses the strategies of hybrid fabrication in which digital technologies are used to promote accuracy and scale whilst the handcrafted methods add individuality, cultural identity, and material expressiveness. The conceptual analysis and comparative discussion help to present, through the research, the ways in which the combination of the digital and traditional approach results in the new expression of visuals, the methods of sustainable production, and the new ways of creative experimentation.